The Development of Autistic Child Caring Model at Sakon Nakhon Hospital - Jaichareon, Vanchai; Nadsantia, Pailin; Boonkong, Piyanuch (Journal of Health Science of Thailand, 2019)
The objective of this participatory action research was aimed to develop an autistic child caring model at Sakon Nakhon hospital employing mixed method including participatory observation, non-participatory observation, group discussions, informal dialogue, sub-group meetings, tape recording, field recording, and in-depth interview during January 2006- August 2007. Researchers were 10 autistic child care-takershouseholders in Sakon Nakhon urban area and a 9-member multi-disciplinary research team. In the two processes of the study - preparation and operation, the latter was divided into 3 sub-processes : situation analysis and system comprehension; planning, feasibility study and feedback of operation; participatory improvement and evaluation. In data analysis, descriptive statistics was employed for quantative part and content analysis for qualitative assessment. It was found that, as a result, an autistic child caring model was developed at Sakon Nakhon hospital with application of the concept of case management with advocacy on a care map, emerging from the participatory process. In due process, empowerment of the autistic child families was maximized through family counseling, the established special child parentsี school for the caretakers; and the library providing borrowing service of books and toys for the development of the underprivileged at home. A one-stop service for handicap registration as well as continuing care in community in collaboration with primary care units, was providecl for this purpose.